PENGARUH KEBERADAAN WISATA TANI (AGROWISATA ) TERHADAP PENDAPATAN PELAKU WISATA TANI PERAH SUSU KAMBING ETAWA (studi kasus : Desa melati Kecamatan Perbaungan) - Irfan Irpan lesmana (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2022)
Melati Village was one of the villages that had many interesting farm tourism locations as well as local wisdom and superior products that were considered to be able to improve the economy. This research was only focused on the attraction of Etawa milking goats. This research used a simple linear regression analysis method and which was analyzed using SPSS 20.0. It was to find out how much influence the existence of farm tourism had on the income of the Etawa milking tourism actors in Melati Village, Perbaungan District. The results of this research indicated that the existence of farm tourism had an effect on the income of the Etawa milking tourism actors in the village of Melati, Perbaungandistrict. tobserved4.979> t table 2.365, meaning that it had a positive and significant effect on the income of the Etawa goat milking tourism actor (Y). The income received by the Etawa goat milking tourism actors was Rp.261.105000/year, and the total average per year was Rp. 37.300.714.or the total average/month obtained by the Etawa farm tourism actors was Rp. 3,108,393.